The influence of body mass index on efficacy and outcomes of percutaneous transforaminal endoscopic surgery (PTES) for the treatment of lumbar degenerative diseases: a retrospective cohort study - Chenyang Zhuang; Yun Xu; Hong Lin; Yutong Gu (BMC Surgery)
Abstract Background To investigate and quantify the influence of body mass index (BMI) on the efficacy and outcomes of percutaneous transforaminal endoscopic surgery (PTES), a novel minimally invasive surgical technique in the treatment of lumbar disc herniation (LDH). Methods A total of 55 patients suffering from single-level LDH with or without high iliac crest, scoliosis or calcification, who underwent PTES in our department from January 2019 to December 2021 were retrospectively analyzed. Patients were divided into two groups according to BMI. The operative events of two groups including X-ray projection, operation time, blood loss and length of stay were compared. Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) were used to evaluate the clinical efficacy and outcomes of the surgery. Differences in complications and recurrences between two groups were also analyzed. Results 55 patients were divided into obese and nonobese groups according to their BMI (33.03 vs. 23.07). There was no significant difference in X-ray projection (times), operation time (mins), blood loss (mL) and length of stay (days) between two groups (7/5–11 vs. 5/5–10, 58.17 ± 9.20 vs. 53.65 ± 10.06, 6.41 ± 1.43 vs. 5.50 ± 2.45, 3.17 ± 1.44 vs. 2.96 ± 0.53, P > 0.05). Both groups demonstrated a significant decrease in ODI (12.01 ± 3.57% vs. 67.16 ± 9.25%, 13.92 ± 4.24% vs. 68.10 ± 9.27%, P < 0.05) and VAS (0.10 ± 0.48 vs. 8.38 ± 0.94, 0.22 ± 0.56 vs. 8.38 ± 0.86) at 24 months after the operation compared with which at the preoperative status. No significant difference in the improvement of the clinical outcomes was found between the two groups in ODI or VAS (P > 0.05). Conclusions With the simple orientation, easy puncture and reduced steps, PTES is an effective and safe method to both obese and normal patients with LDH. Clinical trial number Not applicable.